Association between acculturation surrogates and alcohol consumption in rural-to-urban migrants: The PERU MIGRANT study - Stefan Escobar-Agreda; Alvaro Taype-Rondan; J. Jaime Miranda (Elsevier, 2021)
Introduction: There is a paucity of information about the association between acculturation and alcohol consumption in rural-to-urban migrants who move to urban environments usually characterized by a higher prevalence of alcohol consumption than their rural places of origin. Objectives: To evaluate the cross-sectional association between surrogates of acculturation and alcohol consumption in Peruvian rural-to-urban migrants; to explore the effects of sex and age at migration on these associations; and to explore this association longitudinally. Methods: Data from the PERU MIGRANT Study, which evaluated a cohort of Peruvian rural-to-urban migrants from 2007 to 2012, were analyzed. Four acculturation surrogates were evaluated: language preference on the radio, language spoken at home, Spanish proficiency, and length of residence in urban area. Alcohol consumption was defined as having consumed alcohol in the last year at the time of the baseline survey, while onset of alcohol consumption was defined as having consumed alcohol in the last year at the follow-up survey. Poisson regressions with robust variance were performed to estimate crude and adjusted prevalence ratios (PR) and relative risks (RR) with a 95% confidence interval (95% CI) to cross-sectional and longitudinal analyses respectively. Results: Data from 567 rural-to-urban migrants, mean age 47.6 years (SD ±11.5), 52% females, was included in the study. Crude cross-sectional analyses showed an association between acculturation surrogates and alcohol consumption, but these were not observed in adjusted regressions. In the sex-stratified analyses, only women showed an association between Spanish proficiency and alcohol consumption, where those with higher language proficiency had a 22% higher prevalence of alcohol consumption (PR: 1.22, 95% CI: 1.04-1.43). Analyses stratified by age at migration showed no association between acculturation surrogates and alcohol consumption. On the longitudinal analyses, acculturation surrogates were not associated with the onset of alcohol consumption. Conclusions: No association between acculturation surrogates and alcohol consumption in cross-sectional and longitudinal analyses were found. The only exception was observed in female migrants according to their Spanish proficiency and alcohol consumption .